2011
DOI: 10.1002/uog.10046
|View full text |Cite|
|
Sign up to set email alerts
|

Embryo volume measurement: an intraobserver, intermethod comparative study of semiautomated and manual three‐dimensional ultrasound techniques

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Meaning, a reduction in the rotation angle results in a longer analyzation time, because more planes have to be evaluated [7]. Mean FV calculation time is reported for human fetus measurements and ranges between approximately one to two minutes [10,43] and two to five minutes [8][9][10] for 30° and 9° rotational angles, respectively. No comparative time measurement was found in literature regarding the calculation of a FV with 6° rotational angle in human fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meaning, a reduction in the rotation angle results in a longer analyzation time, because more planes have to be evaluated [7]. Mean FV calculation time is reported for human fetus measurements and ranges between approximately one to two minutes [10,43] and two to five minutes [8][9][10] for 30° and 9° rotational angles, respectively. No comparative time measurement was found in literature regarding the calculation of a FV with 6° rotational angle in human fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional ultrasonography allows scanning and studying fetal structures using the multiplanar view (the three orthogonal planes are displayed in this view). Currently, the most frequently used software to calculate organ or fetal volumes from 3D ultrasonographic datasets is Virtual Organ Computer-aided AnaLysis (VOCAL™, GE Healthcare, Zipf, Austria), which is validated in both in vitro [6,7] and in vivo [8][9][10][11][12] studies in women. With VOCAL™ it is possible to obtain the fetal volume by manually outlining the contour of the fetus in different planes, while the 3D image is rotated about a fixed axis with a selected rotational angle.…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be a significant difference in the volumetry between this semi-automated technique and the conventional VOCAL technique alone with 9A o relations. [50] There was a significant correlation between EV and GA or CRL, [8,19] with a linear association between 11 + 0 weeks and 13 + 6 weeks, [10] or between a CRL of 45 and 84 mm. [10] These findings are consistent with previous 2D sonographic studies on the S-shaped pattern of fetal growth with gestation, with the linear component at 10 and 13 weeks.…”
Section: Embryo or Fetal Volumetrymentioning
confidence: 90%
“…[54] Sono AVC is automatic, but may significantly underestimate GSFV. [50] There is significant correlation between GSFV and GA or CRL. [42] Mean GSFV increased by approximately six to seven-folds from 7.81 to 50.28 cm 3 for a CRL increase from 12 to 40 mm.…”
Section: Gestational Sac Fluid Volumetrymentioning
confidence: 95%
“…Then, the volume is calculated semiautomatically on the basis of a contour drawn by the user on the extracted imaging planes. Thus far, many previous studies have demonstrated the high accuracy and reliability of the VOCAL technique in cases involving fetal organs such as the liver [4,5], lung [6,7], brain [8], bladder [9], and embryo [10], and in phantoms [11,12]. However, thus far, this technique has not been used for measuring the parathyroid gland, and no previous study has compared the virtual volume with the real specimen.…”
Section: Introductionmentioning
confidence: 99%